The Effect of PBL Model Based Local Wisdom Towards Student’s Learning Achievements on Critical Thinking Skills - Khaerus Syahidi; Tsamarul Hizbi; Asriwani Hidayanti; Fartina Fartina (Kasuari: Physics Education Journal (KPEJ), 2020)
This study aims to determine 1) Effect of the Problem Based Learning (PBL) based local wisdom model towards students’ learning achievement 2) Effect of the critical thinking towards students learning achievement 3) Interaction between the use of learning models and critical thinking skills towards student learning achievement. This study was experimental study. The population of this study were all students of class X IPA at SMA AL-Hamzar Tembeng Putik in academic year 2019/2020. The sample of this study was selected by saturated sampling technique which was Class X IPA 1 as an experimental class while class X IPA 2 was as a control class. The research design of this study was 2 x 2 factorial design. the data collection techniques of this study used critical thinking questionnaires and achievement tests. The data were analyzed by using two ways Anova. The results showed that; 1) there was an effect of PBL based local wisdom on student learning achievement, it proved by the result of FA count> Ftable was 11.29> 4.00, which meant H0A was rejected, 2) There was an effect of critical thinking skill towards student learning achievement, it proved by the result of FB> Ftable was 5.51> 4.00 which meant that H0B is rejected. 3) There was no interaction between the use of learning models with the Critical thinking skill towards student achievement, it is because FABcount <Ftable was 0.98 <0.04 which meant H0AB is accepted.